Neuroprotective effect of Bouvardia ternifolia (Cav.) Schltdl via inhibition of TLR4/NF-κB, caspase-3/Bax/Bcl-2 pathways in ischemia/reperfusion injury in rats - Zapata-Lopera, Yury Maritza; Trejo-Tapia, Gabriela; Cano-Europa, Edgar; Rodríguez-Hernández, Aida Araceli; Rojas-Franco, Placido; Herrera-Ruiz, Maribel; Jiménez-Ferrer, Enrique (Frontiers in Pharmacology, 2024)
Bouvardia terniflora dichloromethane extract decreased oxidant stress markers, altered the redox environment, and activated antioxidant enzymes, protecting neurons against damage induced by ischemia/reperfusion. It reduced the expression of inflammatory markers associated with the NF-κB pathway, apoptosis, and glial activation while modulating the production of proteins such as COX-2, iNOS, nNOS, NF-κB, and TLR4. In the BCCAO/reperfusion model, the mechanism of action by which the compounds present in the dichloromethane extract intervene involves different signaling pathways. Initially, they prevented the activation of iNOS and nNOS proteins, leading to decreased production of reactive oxygen and nitrogen species, lipid peroxidation, and the activation of antioxidant enzymes such as catalase and superoxide dismutase. The reduction in oxidant stress decreased expression of proteins and genes involved in apoptosis, such as Bax, Bcl-2, and caspase-3. Additionally, the compounds in the extract acted by inhibiting the TLR4 receptor, impeding the translocation of the transcription factor NF-κB to the nucleus and, consequently, inhibiting inflammatory mediators like IL-1β, IL-6, TNF-α, and COX-2. Moreover, the compounds in the dichloromethane extract attenuated the activation of microglia and astrocytes, as reflected in the reduced expression of glial activation genes such as GFAP and AiF1.